Análise por computadores digitais de estruturas reticuladas no espaço, com elemento de secção variável - Charone Filho, Nagib (1971)
The scope of this paper is to organize a computer program for three dimensional structural frames. The analysis is carried out with the stiffness method. Some arrangements in the stiffness matrix are made in arder to obtain a compact formulation for the problem without loss in generality. These arrangements allow the introduction of hinged members with non-uniform cross section. Also, by using well known techniques , the prograrn allow the introduction of elastic supports, pre-stressing effects, thermal effects and displacements of the supports. This is done in order to give a complete generality to the program. As segments of the program there are subroutines designed to evaluate the reactions of members fixed at both ends, due to external loading. These members may also have non-uniform cross-sections.